E-WOM as the Main Influencer of Surabaya Consumers in Making Purchase Decisions for Fashion Products on Shopee - Sri Utami Ady; Shely Silvia (PT. Anagata Sembagi Education, 2024)
This study is motivated by problems often experienced by fashion product buyers when shopping online, such as products received do not match the picture, have different colors or textures from those seen in online photos, items received are different from orders. This study aims to analyze the effect of price, product quality, and E-WOM on purchasing decisions for fashion products with trust as an intervening variable on the Shopee e-commerce site in the city of Surabaya. This study is a quantitative study with a population of all fashion product consumers from the Shopee e-commerce site who live in the city of Surabaya. The sampling technique used purposive sampling and a sample of 120 respondents was found. The analysis technique used is Structure Equation Models (SEM) using the help of AMOS software version 26. The results of this study indicate that price has a negative but insignificant effect on purchasing decisions. Product quality has a positive but insignificant effect on purchasing decisions. E-WOM has a significant positive effect on purchasing decisions. Price has a positive but insignificant effect on trust. Product quality has a significant positive effect on trust. E-WOM has a significant positive effect on trust. Trust has a significant positive effect on purchasing decisions. Trust does not mediate the effect of price on purchasing decisions. Trust does not mediate the effect of product quality on purchasing decisions. Trust mediates the effect of E-WOM on purchasing decisions. The implication of this study is that e-commerce companies, especially Shopee, should pay more attention to product quality and manage E-WOM well to increase consumer trust, which can ultimately strengthen purchasing decisions. In addition, it is important for companies to ensure that accurate and honest product descriptions are conveyed to consumers, in order to minimize the difference between expectations and reality, and to build and maintain consumer trust.